Tools to Enrich Vulnerability Assessment and Adaptation Planning for Coastal Communities in Data-Poor Regions: Application to a Case Study in Madagascar - Cochrane, K. L.; Rakotondrazafy, H.; Aswani, S.; Chaigneau, T.; Downey-Breedt, N.; Lemahieu, A.; Paytan, A.; Pecl, G.; Plagányi, E.; Popova, E.; van Putten, E. I.; Sauer, Warwick H. H.; et al. (Frontiers in Marine Science, 2019)
Here we describe an interdisciplinary and multi-country initiative to develop rapid, participatory methods to assess the vulnerability of coastal communities and facilitate adaptation to climate change in data-poor regions. The methods were applied in Madagascar as a case study. The initiative centred on an exploratory research exercise in two communities in the south-west of Madagascar, a workshop held in Antananarivo in June 2016, combined with a component on communicating ocean science and climate change to stakeholders. It utilised innovative and rapid approaches to combine global and local skills and information on adaptation and resilience building, taking cognisance of national policies, and was based on the principles of a holistic, integrated and participatory approach. This paper summarises the activities undertaken and assesses how effective they were in achieving the project goals, as well as presenting examples of the outputs obtained. The activities demonstrated the value of using existing high resolution global climate models for provision of information on future trends, and of including a traits-based ecological risk assessment as a standard component of vulnerability assessments. User-friendly qualitative modelling activities helped to consolidate holistic, integrated understanding of selected fisheries. The value of assessing the importance and resilience of supply chains and taking the local management measures and institutions into account were validated. The outcomes of the initiative reinforced the principle that the cumulative ecological and social impacts of individual stressors and drivers on marine-dependent communities must be addressed, including climate-change related stressors. Assessments of vulnerability and adaptation planning should be forward-looking and consider likely changes in the future. They must also be done with participation by local experts and stakeholders to ensure knowledge exchange, local capacity-building and ownership and that outputs are rooted in the local realities, are accepted as being legitimate, and reinforce and complement relevant legal frameworks and laws.